Local Wisdom-Based Entrepreneurship: Sengkuang 76 Coffee Business Strategy In The Modern Era - Prawijaya, Bambang Siswan; Soleh, Ahmad; Hardinata, Dodi (Utami Publisher, 2025)
The application of entrepreneurial orientation is very important for business people. The high competition requires business actors to always provide strategies and innovations to the business being run. The strategies and innovations carried out certainly do not forget the values of local wisdom found in the local community. This condition leads to coffee producers in Kepahiang Regency, one of which is Sengkuang Coffee 76 on strategies based on local wisdom orientation. Many studies on local wisdom are associated with positive values, habits and traditions of a community from a social, cultural and environmental perspective. Coffee is one of the leading commodities in Kepahiang Regency. Coffee farming in Kepahiang Regency has been practiced for generations. This research aims to find out how the strategies carried out by coffee producers in running their business without losing the values of local wisdom. This research uses qualitative methods by using research instruments of interviews, observation and documentation studies. The results of data analysis in this study using descriptive qualitative research results explain that what are the strategies of the sengkuang 76 coffee business in running its business in the modern era without eliminating local wisdom values.